2020
DOI: 10.3390/ijms21134670
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Findings by Computed Tomography in SARS-CoV-2 Patients: Increased Risk of Muscle Wasting in Obesity

Abstract: Obesity is a characteristic of COVID-19 patients and the risk of malnutrition can be underestimated due to excess of fat: a paradoxical danger. Long ICU hospitalization exposes patients to a high risk of wasting and loss of lean body mass. The complex management precludes the detection of anthropometric parameters for the definition and monitoring of the nutritional status. The use of imaging diagnostics for body composition could help to recognize and treat patients at increased risk of wasting with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 48 publications
1
98
2
3
Order By: Relevance
“…Initial data analysis was performed in the CFX96 Manager software prior, followed by export to the Seegene viewer software. The SARS-CoV-2 results were automatically categorised by the 'Seegene viewer' software as '2019-nCoV detected', 'negative' or 'invalid' based on predefined parameters (Allplex 2019-nCoV assay IFU) [36].…”
Section: Patient Population and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial data analysis was performed in the CFX96 Manager software prior, followed by export to the Seegene viewer software. The SARS-CoV-2 results were automatically categorised by the 'Seegene viewer' software as '2019-nCoV detected', 'negative' or 'invalid' based on predefined parameters (Allplex 2019-nCoV assay IFU) [36].…”
Section: Patient Population and Treatmentmentioning
confidence: 99%
“…Fifty-two patients with similar clinical/radiological features were hospitalized in the Grand Metropolitan Hospital starting on March 10 th , 2020 and were considered as the historical control of the study. Forty-nine of the latter patients, who required oxygenation with Ventimask (41 cases) or CPAP with helmet (8 cases), were hosted in the Infectious Diseases/Covid19Operative Unit while 3 further patients requiring mechanic ventilation, were hosted in the Covid19 Resuscitation Unit [36]. The latter patients had received specific treatment with HC, AZM, LMWH (40 cases) and Tocilizumab (12 cases) and none of them received adenosine.…”
Section: Patients Populationmentioning
confidence: 99%
“…1 Nutritional status was found to be associated with the novel Coronavirus disease 2019 (COVID-19) severity, and malnutrition might play a role in this regard, but this aspect was investigated in a limited number of studies. [2][3][4] Previous studies have shown that malnutrition represents an independent risk factor for the prognosis of various infectious diseases including pneumonia. 5 Nutritional risk screening tools are useful in the everyday clinical practice to promptly detect potential or evident malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Factors concurrent to the COVID-19 cytokine storm are several. These include obesity and its comorbidities [ 102 , 103 , 104 , 105 ], a pathological condition that can no longer be overlooked given the cost of human lives paid.…”
Section: Resultsmentioning
confidence: 99%